A Case of Successful Treatment of Left Ventricular Rupture after Transcatheter Aortic Valve Implantation - Tuleutayev, Rustem; Abzaliyev, Kuat; Kolesnikov, Alexey; Kim, Igor; Abzaliyeva, Symbat (Acta medica Lituanica, 2024)
Background: The article talks about a patient who had nonrheumatic disease of the aortic valve and had a left ventricular rupture during a transcatheter aortic valve implantation (TAVI) procedure. Methods: The discrepancy between the size of the prosthesis and the size of the native aortic valve (mismatch) led to the need to deploy a second prosthesis, which was dislocated into the left ventricular cavity and led to myocardial damage and the development of tamponade. Results: As a result of timely cardiac surgery and effective measures of the emergency support service, both prostheses were removed from the left ventricular cavity, the aortic valve was replaced with a “Medtronic Hankock No. 25” biological prosthesis, and the left ventricular myocardial rupture was sutured. Conclusions: In case of the development of such complications during the transcatheter aortic valve implantation (TAVI) procedure with asystole and cardiac tamponade, it was suggested to conduct cardioplegia (instead of chest compressions).
Keywords: TAVI; transcatheter aortic valve implantation; aortic valve; prosthesis dislocation; left ventricular rupture